Implementation of the right to free movement of workers in the East African Community: Examination of the law and practice - Makoko, Charles Elirehema (Mzumbe University, 2026)
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy of Mzumbe University